Trainees' self‐evaluation of their development as psychotherapists: An Italian contribution to an international collaborative study on psychotherapy training. (25th December 2017) - Messina, Irene; Gelo, Omar C. G.; Sambin, Marco; Bianco, Francesca; Mosconi, Andrea; Fenelli, Antonio; Curto, Marcello; Gullo, Salvo; Orlinsky, David
Abstract : This study presents a pilot contribution to the new collaborative, multinational study of psychotherapy trainee development that was undertaken by the Society for Psychotherapy Research Interest Section on Therapist Training and Development (see Orlinsky, Strauss, Rønnestad, et al., 2015 ). Although the main project is longitudinal in design, this preliminary study investigated cross‐sectional differences between trainees in different years of training and explored the influence of core training experiences—including supervision and personal therapy—on their perceived development as therapists. Using the trainee current‐progress report that was designed for the Society for Psychotherapy Research Interest Section on Therapist Training and Development project, 90 trainees at 4 different 4‐year training programs in Italy provided self‐evaluations of their development and of their therapeutic work experiences. Perceived development included overall change, progress, deterioration, overcoming past limitations, and realization of potential as a therapist. Therapeutic work experiences were assessed using scales of healing and stressful involvement (Orlinsky & Rønnestad, 2005 ). Year in training and support in supervision predicted perceived development and healing involvement, whereas experiencing criticism in supervision was associated with stressful involvement. Having had personal therapy, and especially ratings of benefit from personal therapy, was also associated with perceived development and healing involvement. Results are discussed with regard of their implications for psychotherapy training.